Oil palm empty fruit bunch derived microcrystalline cellulose supported magnetic acid catalyst for esterification reaction: An optimization study - Krishnan S.G.; Pua F.-L.; Zhang F. (Elsevier Ltd, 2023)
Calcination; Cellulose; Esterification; Esters; Fruits; Hematite; Molar ratio; Oleic acid; Palm oil; Pore size; Reusability; Acid catalyst; Empty fruit bunches; Esterification of oleic acids; Esterification reactions; Magnetic acid catalyst; Micro-crystalline cellulose; Oil palm; Oil palm empty fruit bunch; Optimisations; ]+ catalyst; Magnetism; Calcination; Cellulose; Esterification; Esters; Fruits; Oleic Acid